FERTILITAS DAN VIABILITAS EMBRIO TELUR ITIK YANG INDUKNYA DIBERI PAKAN SUPLEMENTASI PROBIOTIK - Yunita Rusidah; Yulia Sistina; Ismoyowati Ismoyowati (Universitas Muhammadiyah Kudus, 2017)
AbstrakTujuan penelitian ini adalah untuk mengetahui efek perbedaan dosis pada pakan dengan suplementasi probiotik dan mengetahui dosis yang paling efektif terhadap fertilitas dan viabilitas embrio telur itik (Anas platyrhynchos). Materi penelitian terdiri dari Itik petelur (Anas platyrhynchos) sebanyak 100 ekor dengan rasio sex, jantan : betina = 1 : 5. Bahan pakan sesuai standar SNI formulasi H dan probiotik MEP+. Penelitian eksperimental ini menggunakan Rancangan Acak Lengkap (RAL) dengan 4 perlakuan dan 4 ulangan. Perlakuan terdiri dari : Ro (Kontrol), R1 (Probiotik 0,075 cc/kg pakan), R2 (Probiotik 1,5 cc/kg pakan), R3 (Probiotik 3 cc/kg pakan). Hasil penelitian menunjukan bahwa persentase fertilitas telur itik, secara statistik tidak berbeda nyata (p 0,05). Viabilitas embrionya hingga hari ke-21 inkubasi hasilnya tidak berbeda nyata (p 0,05). Persentase penetasan dan viabilitas embrio setelah periode hari ke-21 hasilnya berbeda nyata (p 0.05), dilihat dari rataan mortalitas embrio terendah perlakuan dosis 0,75 cc/kg pakan (R1) dan penetasan telur itik tertinggi perlakuan dosis 1,5 cc/kg pakan (R2). Parameter pendukung berat telur dan panjang telur secara sangat nyata (p 0,01) dipengaruhi perlakuan, sedangkan analisis data parameter pendukung meliputi, indek telur, lebar telur, kualitas DOD dan bobot DOD, hasilnya tidak berbeda nyata (p 0,05). Hasil uji regresi korelasi data membuktikan bahwa fertilitas dan penetasan, berat telur dan penetasan, bobot DOD dan berat telur terdapat korelasi lemah diantaranya (r 0,06). Key words : Fertilitas, Viabilitas Embrio, probitiotik MEP+ AbstractThis study aims to determine the effect of probiotics as parental food supplementation on fertility and embryo viability of duck eggs (Anas platyrhynchos). More specifically the study aimed to know the dose as well as the most effective dose applied as treatment on the fertility and viability of embryonic duck (Anas platyrhynchos) eggs. Material experimental unit consist of 1 male with 5 female (1:5). Feed ingredients based to SNI standard H formulation and probiotics MEP+. Experimental design usedwas Completely Randomized Design (CRD), four treatments,each with four replications of unit experiments. Experimental unit consist of 1 male with 5 female (1:5). Treatments were : Ro (Control), R1 (0,75 ml probiotic/kg feed), R2 (1.5 ml probiotic/kg feed), R3 (3 ml probiotic/kg feed). Results showed that egg fertility was statistically no significant different (p 0.05) among treatments. Embryo viability up to days 21 of incubation was also statistically no significant different (p 0.05). Hatching rate among treatments as well as embryo viability data after days 21, however, statistically were significant difference (p 0.05). The highest hatching was from treatment of 1.5 ml/kg food (R2) and the lowest mortality of embryos was from 0.75 ml/kg food treated one (R1). Analysis of supporting data (egg width, DOD weight, DOD quality) results in no significant different (p 0.05) among treatments, except for the weight eggs and length eggs data which was highly significance different (p 0.01) among treatments. Regression-Correlation analysis between fertility rate and egg weight, between fertility rate and hatching rate, between hatching rate and eggs weight, between egg weight and DOD weight data, all shown that no such strong correlation at all (r 0.06). Embryo survival at late developmental stages and hatching rate datawere significantlu different (p 0.05) among treatmens. Eggs weight and length were highly significant different (p 0.01) among treatments, proving that probiotic supplementation through parental feeding determined embryo survival and hatching rate of their egg produced. However, this study also proving that fertility rate and viability of early embryo developmental stage data as well as egg width, DOD weight, DOD quality, had no effect after probiotic treatments for 30 days, need further confirmation that probiotic effectively improving reproductive performance (r 0,06). Keywords: fertility, embryo viability, probiotics MEP+.